2010
DOI: 10.1177/0956797610373882
|View full text |Cite
|
Sign up to set email alerts
|

Ways of Giving Benefits in Marriage

Abstract: Couples reported on bases for giving support and on relationship satisfaction just prior to and approximately 2 years into marriage. Overall, a need-based, noncontingent (communal) norm was seen as ideal and was followed, and greater use of this norm was linked to higher relationship satisfaction. An exchange norm was seen as not ideal and was followed significantly less frequently than was a communal norm; by 2 years into marriage, greater use of an exchange norm was linked with lower satisfaction. Insecure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…In a 7-day diary study, breast cancer patients felt greater intimacy on days when their spouses reported providing support (vs. on days when they did not provide support), and spouses showed a parallel pattern (Belcher et al, 2011). Overall, partner responsiveness and support, both central constructs in attachment theory and relationship science in general (Clark & Lemay, 2010), appear important to relationship functioning in couples coping with cancer (addressing Paths c–e in Figure 1), a finding that should generalize to other illnesses and health issues.…”
Section: Applications Of the Model To Adult Health Issuesmentioning
confidence: 93%
See 1 more Smart Citation
“…In a 7-day diary study, breast cancer patients felt greater intimacy on days when their spouses reported providing support (vs. on days when they did not provide support), and spouses showed a parallel pattern (Belcher et al, 2011). Overall, partner responsiveness and support, both central constructs in attachment theory and relationship science in general (Clark & Lemay, 2010), appear important to relationship functioning in couples coping with cancer (addressing Paths c–e in Figure 1), a finding that should generalize to other illnesses and health issues.…”
Section: Applications Of the Model To Adult Health Issuesmentioning
confidence: 93%
“…In addition, this general framework offers a launching point for generating a variety of specific hypotheses and more specific models. For example, researchers might examine the effects of individual differences in communal/exchange orientation (Clark & Mills, 1979) or relational goals (Canevello & Crocker, 2011), either alone or together with attachment style (e.g., Clark, Lemay, Graham, Pataki, & Finkel, 2010) on downstream outcomes in the model.…”
Section: Theoretical Framework For Investigating Relationship Processmentioning
confidence: 99%
“…In contrast, in exchange relationships, benefits are given with the expectation of direct reciprocation, with partners tracking benefits in order to keep things even (Clark & Mills, 2012;Mills & Clark, 1986). Romantic partners indicate that following communal norms (i.e., giving benefits to improve a partner's welfare), as opposed to exchange norms (i.e., giving benefits with the expectation that similar benefits will be reciprocated), is ideal in long-term relationships as they create opportunities for couples to engage in mutually enjoyable activities that meet both partners' needs (Clark, Lemay, Graham, Pataki, & Finkel, 2010).…”
Section: Applying Communal Theory To Sexualitymentioning
confidence: 99%
“…It is also possible that sexual communal motivation changes over the course of a relationship and as result of relationship transitions, such as the transition to marriage or the transition to parenthood. Research on general communal motivation suggests that although people report that communal norms are ideal to follow in long-term relationships, couples tend to adopt more exchange norms following the transition to marriage (Clark et al, 2010). It is possible that this is the result of having to navigate more shared household tasks and co-parenting responsibilities as a relationship progresses, which may make people rely more on notions of equity and tracking and trading so tasks are divided evenly.…”
Section: Implications and Future Directionsmentioning
confidence: 99%
“…The relationships literature suggests that in longer term healthy relationships, people switch from pure social exchange norms where costs and benefits are counted to more noncontingent response patterns (Clark et al 2008; Clark et al 2010; Clark and Mills 2012). This framework is more appropriate for longitudinal panel studies, where the investigator–participant relationship ceases to be short term.…”
Section: Overviewmentioning
confidence: 99%